A NEW APPROACH TO PREDICTING THE RISK OF CHRONIC MESOTYMPANITIS RECURRENCE IN PATIENTS OF DIFFERENT SEXES USING REGRESSION ANALYSIS - Herasymiuk, Maksym (Eastern Ukrainian Medical Journal, 2026)
Chronic mesotympanitis is a variant of chronic suppurative otitis media, accompanied by perforation of the tympanic membrane in the stretched part and characterized by decreased hearing acuity, otorrhea, intoxication syndrome, a feeling of "stuffiness" in the ear, and noise of various nature. The aim of the work is to propose a new approach to predicting the risk of chronic mesotympanitis recurrence depending on the sex of patients using multivariate regression analysis. Materials and methods. We examined and operated on 222 patients (130 women and 92 men) aged 18 to 80 years with a diagnosis of chronic mesotympanitis and underwent tympanoplasty. Results. Using multivariate regression analysis, 13 factors with a significance level of less than 0.05 for the group of men and 9 factorial characteristics for the group of women were analysed. Histograms of residual deviations of the prediction of chronic mesotympanitis recurrence, as well as normal probability plots, the results of which confirm the statistical hypothesis that the residual deviations correspond to the normal distribution law, were obtained. The coefficient of determination, which shows the proportion of factors taken into account in the prediction, was 0.944 in the group of men and 0.919 in the group of women, which gives grounds to assert that 94.4% of factors in the group of men and 91.9% in the group of women, respectively, were taken into account in the model for predicting recurrence of chronic mesotympanitis and that it is highly reliable and acceptable in general. Conclusions. The use of a mathematical model of multifactorial regression analysis, which considers the most likely risk factors for the recurrence of chronic mesotympanitis, allows for timely prevention of the disease, prevention of potential complications and recurrences, as well as the development of algorithms for preoperative preparation and postoperative rehabilitation.